Comparison of Course Completion and Student Performance through Online and Traditional Courses - Atchley, Wayne; Wingenbach, Gary; Akers, Cindy (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2013)
Enrollment in online courses has outpaced overall university enrollment for the past several years. The growth of online courses does not appear to be slowing. The purpose of this study was to compare course completion and student academic performance between online and traditional courses. Archival data from the host university student records system was collected using the Structured Query Language. Descriptive statistics were used to analyze student characteristics. Chi-square analysis was used to determine if statistically significant differences existed between students enrolled in online and traditional courses when comparing course completion and academic performance. Analysis found statistically significant differences existed in both course completion and academic performance for students enrolled in online versus traditional courses. Additional analysis indicated statistically significant differences existed in course completion by course discipline.